Defective titanium dioxide catalyst and preparation and application thereof
Patent Information
- Application Number
- CN202611393582.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]发明构思:本发明选用低成本、化学性能稳定的二氧化钛为基底,通过电合成羟基自由基的缺陷型二氧化钛催化剂,该催化剂通过在二氧化钛中依次进行两次还原处理并结合超低浓度过渡金属掺杂,从而构筑出超高含量的氧空位缺陷,适配电化学三电子氧还原原位产羟基自由基水处理场景,从而解决现有催化材料成本高、选择性差、适配工况窄的技术难题
[0031] (1) The catalyst provided by this invention can efficiently degrade a variety of pollutants, and the degradation efficiency is high. At a current of 10 mA cm⁻¹ -2Under pH=5 conditions, the degradation rates of pollutants tetracycline, rhodamine B, and sulfamethoxazole reached as high as 100%, 100%, and 85%, respectively. Furthermore, the degradation was relatively rapid, achieving 100% degradation of tetracycline and rhodamine B within 100 minutes.
Smart Images

Figure CN122912832A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of three-electron oxygen reduction water treatment, specifically to a defective titanium dioxide catalyst, its preparation method, and its application in three-electron oxygen reduction water treatment. Background Technology
[0002] Hydroxyl radicals possess extremely strong oxidizing properties, react rapidly, and produce no secondary pollution. They are the core active species in advanced oxidation water treatment technologies, capable of efficiently degrading recalcitrant organic pollutants such as dyes, antibiotics, phenols, and pesticides in water bodies. They have irreplaceable application value in fields such as advanced industrial wastewater treatment and water environment remediation.
[0003] Currently, in-situ preparation of hydroxyl radicals in industrial systems mainly relies on three processes: external hydrogen peroxide activation, traditional Fenton, and conventional electro-Fenton. Among them, the conventional electro-Fenton system follows a two-electron oxygen reduction pathway, first generating hydrogen peroxide intermediates, and then relying on the dissolution of ferrous ions to catalyze the production of hydroxyl radicals. This process has several inherent defects: first, high hydrogen peroxide conversion loss and low effective utilization rate; second, the reaction system is only suitable for strongly acidic and narrow operating conditions, and the catalytic activity is significantly reduced in neutral and alkaline water bodies; third, the reaction continuously generates iron sludge solid waste, leading to solid waste disposal and secondary pollution problems; at the same time, it also has shortcomings such as low oxidant generation efficiency and rapid decay of electrode activity.
[0004] In contrast, electrochemical oxygen reduction can be achieved through 3e - The transfer pathway reduces oxygen to a hydroxyl radical in one step (i.e., three-electron redox), and its reaction equation is (O2 + 3e-electron radical). - + 3H + → ·OH + H2O), the reaction process does not require the addition of external hydrogen peroxide, and can continuously produce strong oxidizing hydroxyl radicals in situ in an aqueous system. It has outstanding advantages such as being clean and pollution-free, having high reaction efficiency, low energy consumption, and being able to treat wastewater on-site in a decentralized manner.
[0005] Existing catalytic materials for three-electron oxygen reduction have significant shortcomings: precious metal-based catalysts are scarce and costly to prepare, making large-scale application difficult; pure carbon-based materials have weak adsorption and activation capabilities for oxygen molecules, resulting in poor selectivity and insufficient catalytic activity for three-electron oxygen reduction; existing modified titanium dioxide catalytic systems mostly employ sol-gel hydrothermal combined with air calcination processes or single-step hydrothermal synthesis processes, which are only suitable for photocatalytic degradation or anodic water oxidation to produce hydrogen peroxide, and cannot construct a defect- and metal-synergistic active structure adapted to cathode three-electron oxygen reduction. Summary of the Invention
[0006] Purpose of the invention: The technical problem to be solved by the present invention is to provide a defective titanium dioxide catalyst and its preparation and application, in order to address the shortcomings of the prior art.
[0007] Inventive Concept: This invention uses low-cost, chemically stable titanium dioxide as a substrate and electrosynthesizes a defect-type titanium dioxide catalyst for hydroxyl radicals. This catalyst is constructed by performing two reduction treatments on titanium dioxide and combining them with ultra-low concentration transition metal doping, thereby creating an ultra-high content of oxygen vacancy defects. It is suitable for in-situ electrochemical three-electron oxygen reduction to generate hydroxyl radicals in water treatment scenarios, thus solving the technical problems of high cost, poor selectivity and narrow adaptability of existing catalytic materials.
[0008] To address the aforementioned technical problems, this invention discloses a method for preparing a defective titanium dioxide catalyst.
[0009] The method includes:
[0010] (1) TiO2 is calcined in a first reducing atmosphere to obtain the product after the first calcination, namely TiO2. 2-x -R1, the TiO product after the first calcination 2-x -R1 was dispersed in a precursor solution containing a transition metal salt to obtain a mixed solution; the resulting mixed solution was dried, and the powder, i.e., TiO2 after nickel salt doping, was collected. 2-x -R1;
[0011] (2) The obtained powder is subjected to a second calcination under a second reducing atmosphere to obtain the product of the second calcination, namely nickel-doped TiO2 after calcination. 2-x -R1, the nickel-doped TiO2 after the second calcination product has been calcined. 2-x -R1 was dispersed in acid, washed with water, and dried to obtain the defective titanium dioxide catalyst TiO2. 2-x -R3.
[0012] The first reducing atmosphere and the second reducing atmosphere are both mixtures of hydrogen and argon, and the hydrogen content in the mixture is 5-15% v / v, such as 10% v / v.
[0013] The temperatures of the first and second calcinations are independently selected from 450-800 ℃, such as 500 ℃, 550 ℃, 600 ℃, 650 ℃, 700 ℃, and 750 ℃; the heating rates to the temperatures are independently selected from 2-8 ℃ / min, such as 3 ℃ / min, 5 ℃ / min, and 7 ℃ / min; and the times of the first and second calcinations are independently selected from 1.5-5 h, such as 2 h and 2.5 h.
[0014] In step (1), the transition metal is any one or a combination of iron, cobalt, manganese and nickel, and the transition metal salt is a chloride salt; the iron salt is a divalent or trivalent salt, the cobalt salt is a divalent salt, the manganese salt is a divalent salt, and the nickel salt is a divalent salt, such as nickel chloride hexahydrate; the solvent of the precursor solution is an alcohol, such as a C1-C3 alcohol, such as ethanol.
[0015] In step (1), the molar ratio of TiO2 to transition metal is 130-170:1, such as 145-155:1; the concentration of transition metal salt in the precursor solution is 1.8-3.8 mmol / L, such as 2.5-3.1 mmol / L.
[0016] Furthermore, when the transition metal salt is nickel chloride hexahydrate, in step (1), the mass ratio of TiO2 to nickel chloride hexahydrate is 1:0.01-0.1, such as 1:0.02 or 1:0.05; the precursor solution is an ethanol solution of nickel chloride hexahydrate with a concentration of 0.3-1.2 mg / mL, such as 0.4 mg / mL, 0.7 mg / mL or 1.0 mg / mL.
[0017] In step (1), the drying process involves removing ethanol from the mixed solution, which can be achieved by drying under a sodium lamp.
[0018] In step (2), the acid is hydrochloric acid, which can be selected as 0.5-3 mol / L hydrochloric acid, such as 1 mol / L hydrochloric acid.
[0019] The mass-to-volume ratio of TiO2 to acid is 1 g: 50-300 mL, such as 1 g: 100-200 mL.
[0020] The defective titanium dioxide catalyst provided by this invention has an oxygen defect rate of 0.3-0.4 on its surface, such as 0.3619. The catalyst uses abundant oxygen vacancies as its main active sites, enabling it to drive the three-electron oxygen reduction process, activating oxygen in situ to generate hydroxyl radicals, thereby achieving efficient pollutant degradation and water treatment.
[0021] In some specific embodiments, the preparation method of the defective titanium dioxide catalyst, which involves performing two reduction treatments on titanium dioxide in sequence and combining them with ultra-low concentration transition metal doping to construct an ultra-high content of oxygen vacancies, specifically includes the following steps:
[0022] (1) TiO2 is evenly placed in an alumina crucible and calcined in a tube furnace under a reducing atmosphere to obtain TiO2. 2-x -R1; Dissolve nickel chloride hexahydrate in anhydrous ethanol and sonicate until the nickel chloride hexahydrate dissolves to obtain a precursor solution; calcined TiO2... 2-x-R1 was dispersed in anhydrous ethanol containing nickel chloride hexahydrate and ultrasonically dispersed until TiO2 was obtained. 2-x -R1 is uniformly dispersed in the precursor solution; the mixed precursor solution is dried under a sodium lamp until anhydrous ethanol evaporates, and the powder is collected.
[0023] (2) The collected powder was calcined in a tube furnace under a reducing atmosphere and dispersed in hydrochloric acid with stirring. The acid was then washed away by filtration with deionized water until the pH was neutral. After drying, TiO2 catalyst rich in oxygen vacancies was obtained. 2-x -R3.
[0024] In a second aspect, the present invention discloses a defective titanium dioxide catalyst prepared by the method described in the first aspect above.
[0025] Thirdly, the present invention discloses the application of the defective titanium dioxide catalyst described in the second aspect above in the degradation of pollutants.
[0026] Specifically, the defective titanium dioxide catalyst catalyzes the generation of hydroxyl radicals from oxygen to degrade pollutants. In particular, the defective titanium dioxide catalyst catalyzes the generation of hydroxyl radicals from oxygen in situ through a redox pathway to degrade pollutants, that is, the generation of hydroxyl radicals in situ through three-electron oxygen reduction.
[0027] The contaminants include, but are not limited to, antibiotics and dyes; the antibiotics include tetracycline, the dyes include rhodamine B and sulfonamide dyes, and the sulfonamide dyes include sulfamethoxazole.
[0028] In this invention, x represents the oxygen vacancy content, 0 < x < 1, R represents reduction, and n in Rn represents the sample number.
[0029] Compared to traditional electro-Fenton systems, which are highly dependent on ferrous ions, only adaptable to a narrow acidic range, and have insufficient degradation efficiency for organic pollutants, the defective titanium dioxide catalyst described in this invention not only significantly improves free radical generation efficiency and greatly enhances pollutant degradation rates, but also adapts to wastewater treatment systems with a wide pH range of 3-9 and exhibits good tolerance to actual wastewater containing various anionic and ionic interference ions. Therefore, this technology has outstanding practical value and promising prospects for industrial application in the field of advanced treatment of industrial organic wastewater.
[0030] Beneficial effects:
[0031] (1) The catalyst provided by this invention can efficiently degrade a variety of pollutants, and the degradation efficiency is high. At a current of 10 mA cm⁻¹ -2Under pH=5 conditions, the degradation rates of pollutants tetracycline, rhodamine B, and sulfamethoxazole reached as high as 100%, 100%, and 85%, respectively. Furthermore, the degradation was relatively rapid, achieving 100% degradation of tetracycline and rhodamine B within 100 minutes.
[0032] (2) The catalyst provided by the present invention has high practical application prospects. It not only resists the interference of multiple ions, but also shows good degradation efficiency in the presence of multiple ion interference. It can also stably degrade in cycles, and its properties remain relatively stable after 10 cycles. Attached Figure Description
[0033] Figure 1 (a) TiO2, TiO 2-x -R1, TiO 2-x -R2, TiO 2-x -R3, TiO 2-x X-ray diffraction (XRD) pattern of R3(N2) catalyst; (b) TiO2, TiO 2-x -R1, TiO 2-x -R2, TiO 2-x Raman spectrum of the -R3 catalyst (Raman).
[0034] Figure 2 TiO 2-x TEM image and mapping diagram of the -R3 catalyst.
[0035] Figure 3 TiO2, TiO 2-x -R1, TiO 2-x -R2, TiO 2-x -R3, TiO 2-x Rotating ring electrode (RRDE) voltammetry of -R3(N2) and TiO2-Air catalysts.
[0036] Figure 4 (a) TiO 2-x - Hydrogen peroxide yield of R3 catalyst at different catalyst loadings; (b) TiO 2-x - Hydrogen peroxide yield diagram of R3 catalyst at different current densities.
[0037] Figure 5 TiO 2-x - Pollutant degradation diagram of R3 catalyst at different pH values.
[0038] Figure 6 TiO 2-x -R3 quenching experiment diagram.
[0039] Figure 7TiO2, TiO 2-x -R1, TiO 2-x -R2, TiO 2-x -R3, TiO 2-x The poisoning experiment of thiocyanate on the -R3(N2) catalyst (the dashed line represents the LSV curve after the introduction of thiocyanate, and the solid line represents the LSV curve without the introduction of thiocyanate).
[0040] Figure 8 :(ac)TiO 2-x -R3, TiO 2-x -R1, TiO2 catalyst O 1s Ti 2p Ni 2p XPS spectra; (d) Correlation between oxygen vacancies and performance.
[0041] Figure 9 (a) TiO 2-x -R3, TiO 2-x - Cyclic voltammetry curves of R1 and TiO2 catalysts under Ar atmosphere; (b) TiO2 catalysts 2-x -R3, TiO 2-x Cyclic voltammetry curves of R1 and TiO2 catalysts under O2 atmosphere.
[0042] Figure 10 TiO 2-x -R3(N2), TiO 2-x -R3, TiO 2-x -R3(N2), TiO 2-x - Degradation diagram of Rhodamine B by R1 and TiO2 catalysts.
[0043] Figure 11 TiO 2-x - Degradation diagram of various pollutants by the R3 catalyst.
[0044] Figure 12 TiO 2-x - Degradation rate of cation-anion interference of R3 catalyst.
[0045] Figure 13 TiO 2-x -R3 catalyst cyclic degradation diagram. Detailed Implementation
[0046] The present invention can be better understood from the following embodiments. However, those skilled in the art will readily understand that the descriptions in the embodiments are for illustrative purposes only and should not, and will not, limit the invention as detailed in the claims.
[0047] Unless otherwise specified, the experimental methods described in the following examples are conventional methods; unless otherwise specified, the reagents and materials are commercially available.
[0048] Unless otherwise specified, the TiO2 mentioned in the following examples is commercially available.
[0049] The 10% hydrogen-argon mixed atmosphere described in the following examples is a mixture of hydrogen and argon gas, with a hydrogen content of 10% v / v.
[0050] Example 1
[0051] This embodiment provides a method for preparing a defective titanium dioxide catalyst, the specific steps of which are as follows:
[0052] (1) Weigh 1 g of TiO2 powder and place it evenly in an alumina crucible. Calcinate the powder in a tube furnace at 500 °C for 2 h under a 10% hydrogen-argon mixed atmosphere. The heating rate is 5 °C / min. After calcination, cool the powder to room temperature in the furnace under a hydrogen-argon atmosphere to obtain the TiO2 sample. 2-x -R1.
[0053] (2) Dissolve 20 mg of nickel chloride hexahydrate in 30 ml of anhydrous ethanol and sonicate until the nickel chloride hexahydrate dissolves to obtain the precursor solution. The TiO2 sample obtained in step (1) is then... 2-x -R1 was dispersed in anhydrous ethanol containing nickel chloride hexahydrate and ultrasonically dispersed for 1 h until the sample powder was uniformly dispersed in the precursor solution. The mixed precursor solution was then dried under a sodium lamp until the anhydrous ethanol evaporated, and the powder was collected to obtain TiO2 after nickel salt doping. 2-x -R1 catalyst.
[0054] (3) The TiO2 obtained in step (2) after the nickel salt is doped 2-x The R1 catalyst was calcined in a tube furnace at 500 °C for 2 h in a 10% hydrogen-argon mixed atmosphere, with a heating rate of 5 °C / min. After calcination, the catalyst was cooled to room temperature in the furnace under a hydrogen-argon atmosphere to obtain calcined nickel-doped TiO2. 2-x -R1 catalyst.
[0055] (4) The nickel-doped TiO2 obtained in step (3) after calcination 2-x The R1 catalyst was dispersed in 100 mL of 1 mol / L hydrochloric acid and stirred for 30 min. The acid was then washed away by filtration with deionized water until the pH reached 7. The resulting product, a defect-type titanium dioxide catalyst—TiO2, was then placed in a freeze-drying oven to obtain the final product. 2-x -R3.
[0056] Compare with Example 1
[0057] This comparative example is used to compare with Example 1, and the same preparation method is used. The main process is as follows: 1 g of TiO2 powder is weighed and evenly placed in an alumina crucible. It is calcined in a tube furnace at 500 °C for 2 h under a 10% hydrogen-argon mixed atmosphere, with a heating rate of 5 °C / min. After calcination, it is cooled to room temperature in the furnace under a hydrogen-argon atmosphere to obtain the TiO2 sample. 2-x -R1. Then, it was calcined again in a tube furnace at 500 °C for 2 h under a 10% hydrogen-argon mixed atmosphere, with a heating rate of 5 °C / min. The final product TiO was obtained. 2-x -R2.
[0058] Compare with Example 2
[0059] This comparative example is used to compare with Example 1, and the same preparation method is used. The main process is as follows: 1 g of TiO2 powder is weighed and evenly placed in an alumina crucible. It is calcined in a tube furnace at 500 °C for 2 h under a 10% hydrogen-argon mixed atmosphere, with a heating rate of 5 °C / min. After calcination, it is cooled to room temperature in the furnace under a hydrogen-argon atmosphere to obtain the TiO2 sample. 2-x -R1. The mixture was then uniformly dispersed in the precursor from step (2) of Example 1 and ultrasonically dispersed for 1 h. The resulting precursor solution was then dried under a sodium lamp until anhydrous ethanol evaporated, and the powder was collected. It was then calcined again in a tube furnace under a nitrogen atmosphere at 500 °C for 2 h, with a heating rate of 5 °C / min. The calcined product was dispersed in 100 mL of 1 mol / L hydrochloric acid and stirred for 30 min. The acid was then removed by filtration with deionized water until the pH reached 7. The product was then freeze-dried in a freeze-drying oven to obtain the final TiO2 product. 2-x -R3(N2).
[0060] Compare with Example 3
[0061] This comparative example is used to compare with Example 1. The same preparation method is used, and the main process is as follows: 1 g of TiO2 powder is weighed and evenly placed in an alumina crucible. It is calcined in a tube furnace at 500 °C for 2 h in an air atmosphere with a heating rate of 5 °C / min. After calcination, it is cooled to room temperature in a hydrogen-argon atmosphere to obtain the sample TiO2-Air.
[0062] Experimental Example
[0063] 1. XRD phase characterization and Raman spectroscopy
[0064] X-ray diffraction (XRD) was used to analyze TiO2 and TiO2. 2-x -R1, TiO 2-x -R2, TiO 2-x -R3, TiO 2-xPhase characterization was performed using -R3(N2).
[0065] Raman spectroscopy was used to further analyze the changes in lattice defects in TiO2 and TiO2. 2-x -R1, TiO 2-x -R3 was used for phase characterization.
[0066] 2. Microscopic characterization
[0067] TiO2 was studied using transmission electron microscopy (TEM). 2-x -R3 is used for morphological characterization.
[0068] 3. Electrochemical characterization
[0069] All catalyst electrochemical tests were performed using the Shanghai Chenhua CHI760E electrochemical workstation.
[0070] The catalytic performance of the catalyst was characterized using a traditional three-electrode system, employing a rotating ring-disc electrode (RRDE) as the working electrode, a high-purity stone-ground rod as the counter electrode, and a silver chloride electrode as the reference electrode. Before use, the RRDE was preheated with 0.3... Alumina polishing powder was used for initial polishing on nylon cloth, followed by cleaning and then polishing with 0.05... The alumina polishing powder is used for further polishing.
[0071] Preparation of catalyst slurry: 10 mg of catalyst was dispersed in 50... Nafion was dissolved in 2 ml of anhydrous ethanol, and 10 mg of super P was added. The mixture was sonicated for 10 min to obtain a catalyst slurry. 10 mg of the slurry was then taken. The slurry is drop-coated onto the treated RRDE and allowed to dry completely, thus completing the preparation of the working electrode; the slurries for the remaining materials are prepared using the same method.
[0072] Electrode preparation: Take 10 mg of catalyst and 10 mg of super P, add 2 ml of isopropanol, 50 Sonicate for 10 minutes until the catalyst is uniformly dispersed in the solution.
[0073] The ORR testing procedure is as follows: 1) The electrochemical testing system is a three-electrode system (rotating ring disk electrode as the working electrode, carbon rod as the counter electrode, and Ag / AgCl as the reference electrode), and the electrolyte is a 0.05 mol / L K2SO4 solution with pH 5. 2) Before the test, oxygen is continuously introduced into the reactor for 20 min to ensure that the electrolyte solution reaches oxygen saturation. The aeration flow rate is 150~250 mL / min, and oxygen should also be continuously introduced during the test. 3) To evaluate the oxygen reduction catalytic activity, polarization curve testing (LSV) is performed: the voltage scan range is -1.0~0.2 V vs. Ag / AgCl, the scan rate is 1 mV / s, and the rotation speed is 1600 rpm.
[0074] Hydrogen peroxide yield tests under different current densities and catalyst loadings:
[0075] Electrode preparation: Take TiO2 2-x -R3 catalyst 5, 10, 30 or 50 mg, super P 10 mg, added to 2 ml isopropanol, 50 Sonicate for 10 minutes until the catalyst is uniformly dispersed in the solution.
[0076] The steps for hydrogen peroxide yield testing are as follows: 1) The electrochemical testing system is a three-electrode system (catalyst electrode as the working electrode, carbon rod as the counter electrode, and Ag / AgCl as the reference electrode), and the electrolyte is a 0.05 mol / L K2SO4 solution with pH 5. 2) Before the test, oxygen is continuously introduced into the reactor for 20 min to ensure that the electrolyte solution reaches oxygen saturation. The aeration flow rate is 150~250 mL / min, and oxygen should also be continuously introduced during the test. 3) Tests are conducted at different selected current densities, with each sampling interval of 10 min. 4) The sample is placed in a colorimetric tube, and hydrogen peroxide is detected using the potassium titanate method.
[0077] Free radical quenching experiment: at a current density of 10 mA cm⁻¹ -2 Below, catalyst (TiO) 2-x The -R3 electrode sheet was used as the working electrode, the platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode. Different quenchers were added to the reaction system (a 0.05 mol / L K2SO4 solution at pH=5). The concentration of the quencher had to be several times higher than the concentration of free radicals. The degradation effect of pollutants at different time points was then detected by high performance liquid chromatography. The control group was the one without quencher.
[0078] The experimental steps for thiocyanate poisoning are as follows: 1) The electrochemical test system is a three-electrode system (catalyst electrode as the working electrode, carbon rod as the counter electrode, and Ag / AgCl as the reference electrode). The electrolytes are a 0.05 mol / L K₂SO₄ solution with pH 5 and a 0.1 mol potassium thiocyanate solution. 2) Before the test, oxygen is continuously introduced into the reactor for 20 min to ensure that the electrolyte solution reaches oxygen saturation. The aeration flow rate is 150~250 mL / min, and oxygen is continuously introduced during the test. 3) Polarization curve testing (LSV) is performed: the voltage scan range is -1.0~0.2 V vs. Ag / AgCl, the scan rate is 1 mV / s, and the rotation speed is 1600 rpm.
[0079] XPS Testing Procedure: 1) Sample preparation: Dry solid samples are fixed to the sample holder using conductive adhesive; powdered samples are blown away to prevent dust generation, avoiding contact with the test surface throughout the process. 2) The sample is placed in the injection chamber, and after being evacuated to the specified vacuum level, it is transferred to the ultra-high vacuum analysis chamber. 3) The test area is located using optical field of view and height calibration is performed. For insulated samples, the charge neutralization gun is activated to eliminate the charging effect. 4) During testing, a full spectrum is first acquired to qualitatively identify the elements contained in the surface. Then, based on the full spectrum results, a high-resolution narrow spectrum of the target element is acquired to analyze the chemical valence state. 5) After the test, the sample is returned to the injection chamber, and the sample is removed after gas filling. 6) The data is then processed using software, using C 1s Charge correction was performed at (284.8 eV), background was subtracted, and narrow-spectrum peak fitting was performed to calculate the atomic percentage of each component.
[0080] Preparation of catalyst slurry for cyclic voltammetry: 10 mg of catalyst was dispersed in 50 mL of water. Nafion was dissolved in 2 ml of anhydrous ethanol, and 10 mg of super P was added. The mixture was sonicated for 10 min to obtain a catalyst slurry. 10 mg of the slurry was then taken. The slurry is drop-coated onto the treated RRDE and allowed to dry completely, thus completing the preparation of the working electrode; the slurries for the remaining materials are prepared using the same method.
[0081] The procedure for cyclic voltammetry is as follows: 1) The electrochemical testing system is a three-electrode system (catalyst electrode as the working electrode, carbon rod as the counter electrode, and Ag / AgCl as the reference electrode), and the electrolyte is a 0.05 mol / L K₂SO₄ solution with pH 5. 2) For cyclic voltammetry under aerobic conditions, oxygen must be continuously introduced before testing; for cyclic voltammetry under anaerobic conditions, argon must be continuously introduced before testing. 3) Select the test potential for cyclic voltammetry scanning.
[0082] Pollutant degradation test: at a current density of 10 mA cm⁻¹ -2In this study, a catalyst electrode sheet was used as the working electrode, a platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode. Various pollutants were added to the system at a concentration of 10 ppm, and the degradation effect of the pollutants at different time points was detected by high performance liquid chromatography.
[0083] The pollutant degradation test steps are as follows: 1) The electrochemical test system is a three-electrode system (catalyst electrode as the working electrode, carbon rod as the counter electrode, and Ag / AgCl as the reference electrode), and the electrolyte is a 0.05 mol / L K2SO4 solution with pH 5. 2) Oxygen must be continuously introduced during the test. 3) High-performance liquid chromatography (HPLC) is used to detect pollutants. The pollutant concentration is determined by HPLC (Agilent Technologies 1260 Infinity), using a ZORBAX EclipsePlus C18 5... A 4.6 mm × 100 mm column was used at 35 ℃. The mobile phase consisted of acetonitrile, methanol, water, and 0.1% formic acid. 0.1% formic acid and acetonitrile solutions were used as mobile phases A and B, respectively, with elution programs of 80% A and 20% B. The test mobile phase consisted of an aqueous phase (0.1% formic acid solution) and an organic phase (acetonitrile). The steady-state flow rate was 1 mL / min. -1 The injection volume is 5 The test lasted for 6 minutes.
[0084] Anion-cation interference degradation experiment: at a current density of 10 mA cm⁻¹ -2 In this study, a catalyst electrode sheet was used as the working electrode, a platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode. Various anions and cations were added to the system at a concentration of 10 ppm. The degradation effect of pollutants at different time points was detected by high performance liquid chromatography.
[0085] The experimental steps for the degradation experiment involving cation and anion interference are as follows: 1) The electrochemical test system is a three-electrode system (catalyst electrode as the working electrode, carbon rod as the counter electrode, and Ag / AgCl as the reference electrode), and the electrolyte is a 0.05 mol / L K2SO4 solution with pH 5. 2) Oxygen must be continuously introduced during the test. 3) Tetracycline is detected by high-performance liquid chromatography (HPLC). The pollutant concentration is determined by HPLC (Agilent Technologies 1260 Infinity) using a ZORBAX Eclipse Plus C18 5-inch sensor. A 4.6 mm × 100 mm column was used at 35 ℃. The mobile phase consisted of acetonitrile, methanol, water, and 0.1% formic acid. 0.1% formic acid and acetonitrile solutions were used as mobile phases A and B, respectively, with elution programs of 80% A and 20% B. The test mobile phase consisted of an aqueous phase (0.1% formic acid solution) and an organic phase (acetonitrile). The steady-state flow rate was 1 mL / min. -1 The injection volume is 5 The test lasted for 6 minutes.
[0086] Cyclic degradation experiment: at a current density of 10 mA cm⁻¹ -2 The catalyst electrode sheet was used as the working electrode, the platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode. A pollutant concentration of 10 ppm was added to the system. The degradation effect of the pollutant at different times was detected by high performance liquid chromatography. Ten degradation tests were performed on the same working electrode.
[0087] The cyclic degradation experiment test steps are as follows: 1) The electrochemical test system is a three-electrode system (catalyst electrode as the working electrode, carbon rod as the counter electrode, and Ag / AgCl as the reference electrode), and the electrolyte is a 0.05 mol / L K2SO4 solution with pH 5. 2) Oxygen must be continuously introduced during the test. 3) Tetracycline is detected by high-performance liquid chromatography (HPLC). The pollutant concentration is determined by HPLC (Agilent Technologies 1260 Infinity) using a ZORBAX EclipsePlus C18 5. A 4.6 mm × 100 mm column was used at 35 ℃. The mobile phase consisted of acetonitrile, methanol, water, and 0.1% formic acid. 0.1% formic acid and acetonitrile solutions were used as mobile phases A and B, respectively, with elution programs of 80% A and 20% B. The test mobile phase consisted of an aqueous phase (0.1% formic acid solution) and an organic phase (acetonitrile). The steady-state flow rate was 1 mL / min. -1 The injection volume is 5 The test lasted for 6 minutes.
[0088] Figure 1 X-ray diffraction (XRD) and Raman spectroscopy (Raman) patterns of the catalyst confirmed the presence of TiO2 and TiO2. 2-x -R1, TiO 2-x -R2, TiO 2-x -R3, TiO 2-x -R3(N2) has the characteristic peak corresponding to titanium dioxide, confirming the successful synthesis of the material.
[0089] Figure 2 TiO 2-xThe TEM and mapping images of -R3 show that Ni is uniformly dispersed without agglomeration. The diffraction pattern also clearly shows the diffraction rings of titanium dioxide, proving that the modification and metal loading process did not change the main crystal form of TiO2.
[0090] Figure 3 : By using rotating ring disk electrode testing, it can be found that TiO2 2-x The disk current density of R3 is 2.46 mA cm⁻¹. -2 The disk current characteristics belong to the three-electron hydroxyl radical producing catalysts, and are calculated using the KL equation. (TiO2) 2-x The electron transfer number of the R3 material is 2.98, which is close to the theoretical value for 3-electron oxygen reduction, proving that the catalyst possesses 3-electron oxygen reduction capability. More importantly, the catalyst TiO2-Air, obtained by air calcination, shows an electron transfer number close to 3.8 and does not possess efficient 3-electron oxygen reduction capability.
[0091] Figure 4 When the catalyst TiO2 2-x -R3 loading is 10 mg, and current density is 10 mA cm⁻¹. -2 The catalyst exhibits the highest H2O2 yield under these conditions. H2O2 is a key reactant in the reduction of three-electron oxygen, thus indirectly proving that the catalyst has the highest hydroxyl production capacity under these conditions.
[0092] Figure 5 The pollutant degradation performance of the catalyst was tested under pH conditions of 3, 5, 7, and 9, and under oxygen-bearing conditions, an application of 10 mA cm⁻¹ was performed. -2 The current density of TiO was found to be... 2-x The degradation rates of Rhodamine B (RhB) by -R3 were 96%, 100%, 85%, and 67%, respectively, with the highest degradation efficiency observed at pH 5.
[0093] Figure 6 The main active species in the catalytic system were identified through free radical quenching experiments. Introducing tert-butanol (TBA) and methanol (MeOH) into the reaction system to capture hydroxyl radicals significantly inhibited the degradation efficiency of tetracycline (TC); while the degradation performance decreased relatively less with the addition of p-benzoquinone (p-BQ) and bisphenol A (FFA). The experimental results confirm that hydroxyl radicals are the core active species in the electrocatalytic system for the degradation of tetracycline, further demonstrating that the catalyst activates oxygen through a three-electron oxygen reduction pathway to generate ·OH, thereby achieving the oxidative removal of pollutants.
[0094] Figure 7The thiocyanate poisoning experiment confirmed that the oxygen reduction current density decreased only slightly after the introduction of thiocyanate, indicating that although the oxygen reduction pathway was inhibited to some extent, its main activity remained. This result suggests that transition metals are not the key sites driving the three-electron oxygen reduction to generate hydroxyl radicals.
[0095] Figure 8 TiO 2-x -R3, TiO 2-x XPS spectra of the R1 and TiO2 catalysts show that the hydrogen-argon reduction step increases, and the oxygen vacancy content gradually increases. Meanwhile, combined with... Figure 8 (d) Correlation analysis of oxygen vacancy content and performance shows that oxygen vacancy content is positively correlated with electrochemical performance. Therefore, oxygen vacancy is the main active site for efficiently activating O2 and catalyzing the decomposition of intermediate product H2O2 to generate ·OH active species.
[0096] Figure 9 No cathodic reduction peak was observed in any material under Ar atmosphere, but a clear ORR reduction peak appeared under O2 saturation conditions, proving that the reduction signal was generated by oxygen reduction. (Defective TiO2) 2-x - The reduction peak current of the R3 sample is much higher than that of other control materials. This is due to the high concentration of oxygen vacancies induced by the secondary reduction treatment and low-concentration transition metal doping, which significantly improves the O2 reduction kinetics.
[0097] Figure 10 At the optimal current density of 10 mA cm⁻¹ -2 Under the conditions of 10 mg loading and pH 5, the degradation curves of different catalysts for the pollutant Rhodamine B were evaluated. The degradation curves showed that the samples TiO2 and TiO2... 2-x -R1, TiO 2-x -R2, TiO 2-x -R3, TiO 2-x The degradation efficiencies of -R3(N2) after 2 h were 0%, 10%, 89%, 100%, and 13%, respectively, for defective TiO2. 2-x -R3 showed significantly better pollutant removal performance than other control samples.
[0098] Figure 11 At 10 mA cm -2 TiO2 was studied at current density 2-x The degradation effect of the R3 catalyst on tetracycline (TC), rhodamine B (RhB), and sulfamethoxazole (SMX) was observed after 2 hours of degradation on TiO2. 2-x -R3 can remove 100%, 100%, and 85% of the three pollutants, respectively.
[0099] Figure 12To investigate the influence of coexisting ions in actual aquatic environments on the performance of a catalytic system in degrading tetracycline, typical anion-cation interference experiments were conducted. The results showed that under the interference of multiple ions and organic humic acid (Ca... + Mg 2+ Cl - NO3 - HNO3 - HCO3 - The catalyst has almost no negative impact on the removal efficiency of tetracycline, indicating that the catalyst has strong tolerance to common coexisting ions in natural water bodies and has good application potential in the field of actual wastewater remediation.
[0100] Figure 13 At 10 mA cm -2 TiO2 was studied at current density 2-x The cyclic degradation performance of the R3 catalyst for tetracycline was tested, and TiO2 was found to be effective after 10 cycles of degradation. 2-x -R3 reduced the removal rate of tetracycline by only 10%.
[0101] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A method for preparing a defective titanium dioxide catalyst, characterized in that, include: (1) TiO2 is calcined in a first reducing atmosphere, and the product after the first calcination is dispersed in a precursor solution containing a transition metal salt to obtain a mixed solution; the mixed solution is dried and the powder is collected. (2) The obtained powder was calcined for the second time under the second reducing atmosphere. The product of the second calcination was dispersed in acid, washed with water, and dried to obtain a defective titanium dioxide catalyst.
2. The preparation method according to claim 1, characterized in that, The first and second reducing atmospheres are both mixtures of hydrogen and argon, with the hydrogen content in the mixture being 5-15% v / v.
3. The preparation method according to claim 1, characterized in that, The temperatures of the first and second calcinations are each independently selected from 450-800 ℃, and the heating rates to these temperatures are each independently selected from 2-8 ℃ / min; the times of the first and second calcinations are each independently selected from 1.5-5 h.
4. The preparation method according to claim 1, characterized in that, The transition metal is any one or a combination of iron, cobalt, manganese and nickel.
5. The preparation method according to claim 1, characterized in that, In step (1), the molar ratio of TiO2 to transition metal is 130-170:1; the concentration of transition metal salt in the precursor solution is 1.8-3.8 mmol / L.
6. The preparation method according to claim 1, characterized in that, In step (2), the acid is hydrochloric acid, optionally 0.5-3 mol / L hydrochloric acid.
7. The preparation method according to claim 1, characterized in that, The mass-to-volume ratio of TiO2 to acid is 1 g: 50-300 ml.
8. The defective titanium dioxide catalyst prepared by the method according to any one of claims 1-7.
9. The application of the defective titanium dioxide catalyst according to claim 8 in the degradation of pollutants.
10. The application according to claim 9, characterized in that, The defective titanium dioxide catalyst described herein catalyzes the generation of hydroxyl radicals from oxygen to degrade pollutants.